IgG4‐related disease of the paratestis with the scrotal fluid: A case report. Issue 2 (30th October 2018) - Mochizuki, Kunio; Hanai, Yuki; Nakazawa, Kumiko; Murata, Shiori; Kasai, Kazuki; Mochizuki, Naoko; Tahara, Ippei; Kondo, Tetsuo
Abstract: IgG4‐related disease (IgG4‐RD) can affect various organs, and the pancreas and salivary gland are representative examples. We report a rare case of IgG4‐RD of the paratestis. A 74‐year‐old man presented with left scrotal swelling. Scrotopuncture drainage and cytology confirmed a clear, yellow retention liquid (130 mL) with many small, similar lymphocytes and a few plasmacytes. Many lymphoid cells were immunopositive for CD3 on a cell block section, indicating that a predominant type of lymphoid cells was T cell. There were also some CD20 immunopositive cells and a few IgG4 immunopositive cells. Two months later the left scrotal swelling had returned, and he underwent radical inguinal orchiectomy. Microscopically, there was considerable lymphoplasmacytic inflammatory infiltration, fibrosis and abundant IgG4 immunopositive cells in the paratesticular region. The histopathologic and immunohistochemistry findings were consistent with IgG4‐RD. However, the abundant T cells in the scrotal fluid complicated the cytological diagnosis in our case.